Beliefs in health in a young military population, in relation to smoking (UNED Research Journal, 2019)
In the military population, tobacco consumption is associated with age, stress, family separation and team pressure. We applied a survey to 29 Colombian cadets whose average age was 22 years. They associate smoking with self-confidence, insomnia, better digestion and pleasure; as well as with cancer, coughing, throat irritation, lung diseases and brain damage. Nevertheles, 42% have smoked, and consume 1 to 5 cigarettes daily.
Keywords: health promotion; tobacco use disorder; health knowledge; attitudes; practice.